The politics of language oppression in Tibet - Roche, Gerald 1978- (Cornell University Press, 2024)
"Focuses on how Tibet's minority languages are vulnerable to both the Chinese state's aggressive assimilatory policies and a transnational project that resists this assimilation by promoting Tibetan ethnic survival through linguistic homogenization."
Keywords: Linguistic minorities / Political aspects / China / Tibet Autonomous Region; Language policy / Social aspects / China / Tibet Autonomous Region; Endangered languages / Political aspects / China / Tibet Autonomous Region; Tibetan language / Political aspects / China / Tibet Autonomous Region; Bonan language / Political aspects / China / Tibet Autonomous Region; Minorités linguistiques / Aspect politique / Chine / Région autonome du Tibet; Langues menacées / Aspect politique / Chine / Région autonome du Tibet; Tibétain (Langue) / Aspect politique / Chine / Région autonome du Tibet; Baoan (Langue) / Aspect politique / Chine / Région autonome du Tibet; LANGUAGE ARTS & DISCIPLINES / Linguistics / General